Mechanism investigation of thermal degradation of CO2-based poly(cyclohexene carbonate caprolactone). (October 2019) - Xu, Yonghang; Zhang, Tao; Zhou, Yiluan; Zhou, Danmin; Shen, Zixin; Lin, Limiao
Abstract: The thermal degradation behaviors and mechanisms of CO2 -based poly(cyclohexene carbonate caprolactone)s (PCHCCLs) were deeply studied taking advantage of thermogravimetric analysis/Fourier transform infrared spectrometry (TG/FTIR) and pyrolysis gas chromatography/mass spectrometry (Py-GC/MS) techniques. The experimental results indicate that the decomposition temperatures of PCHCCLs increase with the increasing contents of polycaprolactone (PCL) segments. Backbiting reaction was found to be the dominant degradation pathway for PCHCCLs, and a complicated random rupture process was also observed at higher pyrolysis temperature. Highlights: The thermal degradation behaviors and mechanisms of CO2 -based PCHCCLs were inspected via TG/FTIR and Py-GC/MS techniques. The thermal decomposition process of PCHCCL is the combination of PCHC and PCL. Cyclic cyclohexene carbonate derived from backbiting reaction of PCHC segments is the main pyrolyzate at lower temperature. More ε-caprolactone molecules were pyrolyzated at higher temperature.